PENGARUH FAKTOR FUNDAMENTAL MIKRODANMAKROEKONOMITERHADAPRETURNSAHAM - Muhammad Aditiya Anshari; Fifi Swandari; Ali Sadikin (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
The purpose of this research is to analyze the fundamental factor of micro and macroeconomic whichare Return on Asset, Earning Per Share, Debt to Equity Ratio, inflation, rupiah exchange rate and interest rate of Bank Indonesia to stock return. This research used multiple linear regression analysis for the test. The populationis Consumer Goods Industry Company registered in Indonesian Stock Exchange in the period of 2013-2017 and they fulfilled the chosen sample criteria. Twenty three companies were used as sample. The data were collected by taking secondary data from annual report company in the period of 2013-2017 that were published at Indonesian Stock Exchange. The hypothesisof the research was tested by multiple linear regression. The results of the study with the coefficient of determination test (R2) concluded that the return of the consumer goods industry sector can be explained by the six independent variables of 9.6%. The F Test results in this study indicate that micro and macro economic variables (the rate of Return on Assets, Earning Per Share, Debt to Equity Ratio, inflation, rupiah exchange rate and interest rates of Bank Indonesia) as a whole have a signi ﬁ cant effect. T test results The results of the analysis show that Earning Per Share and inflation affect stock returns. The Earning Per Share variable has a significance value of 0.038 smaller than 0.05. Then the inflation variable has a significance value of 0.020 smaller than 0.05. Whereas the other variables in this study are Return on Assets, Debt to Equity Ratio, rupiah exchange rate and Bank Indonesia interest rates that have no effect on stock returns.